Root cause failure investigation of a boiler waterwall tube employed in a 325 MW thermal power plant: Caustic corrosion phenomenon and its effects. (March 2022) - Soltanloo, Mostafa; Babaee, Mohammad Hossein; Hosseini Yeganeh, Sayyed Ehsan; Shafiei, Ali; Akbari, Amir Hossein
Highlights: Failure analysis steps were carried out in sequence in this study. The influence of fire/waterside factors on the failure was characterized. The authors pronounced that the damage was owing to caustic corrosion phenomenon. Abstract: This paper focuses on failure analysis of a boiler waterwall tube, ASTM A213 Grade T2 steel, used in a 325 MW fuel oil-fired thermal power plant. The influence of fire/waterside factors on the failure was identified through multiple characterization techniques. Preliminary macroscopic observations revealed uniform heavy deposition and repair welding indications on the fireside surface of the failed tube. Moreover, a longitudinally hemielliptical inner groove along with excessive weld metal penetration and discrete cavities were observed along the crown of the tube, leading to local wall thinning down to around 50% of its nominal thickness. No noticeable hardness and microstructural variations such as pearlite colonies decomposition caused by long term overheating and formation of decarburized layer were detected. According to the results of micro-zone analyses, considerable quantity of sodium vanadium oxide compounds accumulated throughout the fireside surface of the tube was due to poor fuel quality used. The authors postulated that evaporation at the waterline of the approximately filled tube resulted in water/steam stratification and localized caustic constituents concentration within the inner groove like NaOH and alkaline producing salts containing Na, Mg, Ca and P elements entered into the water/steam cycle through condenser copper-based tube leakages. This trend solubilized protective magnetite film locally and, consequently, triggered caustic corrosion of the bare steel.